Sociological Impact of COVID-19 on People with Non-Communicable Diseases (NCD) and Long COVID-19 in Young Children: Sociological Impact of COVID-19 - ELENGOE, ASITA; Ibrahem, Kamoka; Allaq, Abdulmutalib; Alabed, ALABED (Journal of Tropical Life Science, 2022)
The Coronavirus Disease 2019 (COVID-19) pandemic has posed enormous healthrisks worldwide. In the 21st century, a novel virus which is called SARS-CoV-2; wasthe main cause for the COVID-19 pandemic outbreak. This virus is transmitted fromperson to person through direct and indirect transmission. Some infected people develop serious symptoms, but others do not show any symptoms. Infected people withno visible symptoms could also transmit the viruses. Literature studies about theCOVID-19 pandemic (starts from Dec 2020 until June 2021) were conductedthrough PubMed, Embase, Medline and Google Scholar. In this study, we exploredthe COVID-19's impact on non-communicable diseases and young children. Scientists are currently testing several drugs to eradicate the COVID-19 outbreak. Pfizer,AstraZeneca, Sinovac and Moderna, vaccine doses administrated successfullythroughout the world. Government agencies also implemented certain rules and regulations to protect their citizens from coronavirus. Moreover, World Health Organization (WHO) also helps by providing many valuable information and precautionsto countries. Hence, this study might provide some information on how to deal withthe virus to curb the rapid spread of the SARS-CoV-2.Keywords: COVID-19, Non-communicable diseases, SARS-CoV-2, Young children